Periodic points of equivariant maps - Jezierski, Jerzy; Marzantowicz, Waclaw (Mathematica Scandinavica, 2010)
We assume that $X$ is a compact connected polyhedron, $G$ is a finite group acting freely on $X$, and $f:X→ X$ a $G$-equivariant map. We find formulae for the least number of $n$-periodic points in the equivariant homotopy class of $f$, i.e., $\inf_h |(Fix(h^n)|$ (where $h$ is $G$-homotopic to $f$). As an application we prove that the set of periodic points of an equivariant map is infinite provided the action on the rational homology of $X$ is trivial and the Lefschetz number $L(f^n)$ does not vanish for infinitely many indices $n$ commeasurable with the order of $G$. Moreover, at least linear growth, in $n$, of the number of points of period $n$ is shown.